Previous cervical cytology and high-risk human papillomavirus testing in a cohort of patients with invasive cervical carcinoma in Shandong Province, China. - Liran Zhang; Fengxiang Xie; Xinguo Wang; Dezhi Peng; Chunrui Bi; Lingbo Jiang; Dongman Zhao; Xinxin Tian; Debo Qi (PLoS ONE)
Background Currently, available data regarding previous cervical cytology and high-risk human papillomavirus (hrHPV) test results to detect invasive cervical cancer are limited and controversial in China. Therefore, this retrospective study in a population of Chinese women with invasive cervical carcinoma aimed to gain further insight into the roles of cytology and hrHPV testing in cervical cancer screening. Methods A total of 1214 cases with a histological diagnosis of invasive cervical cancer were retrieved from the Pathology Database of Jinan KingMed Diagnostics (JKD) over a 5-year period. Previous cytology and hrHPV test results of 469 patients carried out within the year before cancer diagnosis were documented. Results A higher percentage of patients who had undergone prior screening had micro-invasive cervical carcinoma than patients who had no prior screening (25.4% vs. 12.1%, P < 0.001). Of the 469 patients with available prior screening results, 170 had cytology alone, 161 had hrHPV testing alone, and 138 had both cytology and hrHPV testing. There was a significantly lower percentage of hrHPV-positive cases with adenocarcinoma than with squamous cell carcinoma (77.8% vs. 96.4%, P = 0.001). The hrHPV test showed a significantly higher sensitivity than cytology alone (94.4% vs. 85.3%, P = 0.006). The overall sensitivity of the combination of cytology and hrHPV testing (98.6%) was much higher than that of cytology alone (P < 0.001) but only marginally higher than that of hrHPV testing alone (P = 0.058). Conclusions The results revealed that prior cervical screening can detect a significantly larger number of micro-invasive cervical cancers. The hrHPV test can provide a more sensitive and efficient strategy than cytology alone. As the addition of cytology to hrHPV testing can only marginally increase the efficiency of the hrHPV test, hrHPV testing should be used as the primary screening approach, especially in the low-resource settings of China.